2016
DOI: 10.1080/15284336.2015.1126424
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Recombinant Human Growth Hormone and Rosiglitazone for HIV-Associated Abdominal Fat Accumulation on Adiponectin and other Markers of Inflammation

Abstract: Background/Objective In a previous report of HIV-infected patients with fat redistribution, we found that recombinant human growth hormone (rhGH) therapy reduced visceral adipose tissue (VAT) but increased insulin resistance, and that the addition of rosiglitazone reversed the negative effects of rhGH on insulin sensitivity. In this study, we sought to determine the effects of recombinant human growth hormone (rhGH) and rosiglitazone therapy on an array of inflammatory and fibrinolytic markers. Methods 72 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Of particular importance, it was reported that PPARy inhibits Th17 effector functions by the transcriptional repression of RORyt [32,34], the master regulator of Th17 differentiation [14,15]. Clinical trials were previously performed using PPARy agonists/activators, for example, rosiglitazone (RGZ) for treating the lypodystrophy caused by specific classes of antiretroviral drugs [35], as well as metabolic syndrome and inflammation in HIV-infected individuals [36][37][38][39]. However, to our knowledge, no clinical trials were performed using PPARy targeting drugs in the context of HIV cure/remission strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular importance, it was reported that PPARy inhibits Th17 effector functions by the transcriptional repression of RORyt [32,34], the master regulator of Th17 differentiation [14,15]. Clinical trials were previously performed using PPARy agonists/activators, for example, rosiglitazone (RGZ) for treating the lypodystrophy caused by specific classes of antiretroviral drugs [35], as well as metabolic syndrome and inflammation in HIV-infected individuals [36][37][38][39]. However, to our knowledge, no clinical trials were performed using PPARy targeting drugs in the context of HIV cure/remission strategies.…”
Section: Introductionmentioning
confidence: 99%